Validation of the Japanese Big Five Scale Short Form in a University Student Sample - Toyomoto, Rie; Sakata, Masatsugu; Yoshida, Kazufumi; Luo, Yan; Nakagami, Yukako; Iwami, Taku; Aoki, Shuntaro; Irie, Tomonari; Sakano, Yuji; Suga, Hidemichi; Sumi, Michihisa; Ichikawa, Hiroshi; et al. (Frontiers in Psychology, 2022)
The Japanese Big Five Scale Short Form (JBFS-SF), a 29-item self-report scale, has recently been used to measure the Big Five personality traits. However, the scale lacks psychometric validation. This study examined the validity and reliability of the JBFS-SF with data collected from 1,626 Japanese university students participating in a randomized controlled clinical trial. Structural validity was tested with exploratory and confirmatory factor analysis and measurement invariance tests were conducted across gender. Internal consistency was evaluated with Cronbach's α coefficients. Additionally, construct validity was estimated across factors using the PHQ-9, GAD-7, AQ-J-10 and the SSQ. EFA results showed that the JBFS-SF can be classified according to the expected five-factor structure and three items had small loadings. Therefore, we dropped these three items and tested reliability and validity of the 26-item version. CFA results found that a 26-item JBFS-FS has adequate structural validity (GFI = 0.907, AGFI = 0.886, CFI = 0.907, and RMSEA = 0.057). The Cronbach's α of each factor was 0.76-0.86. Each Big Five Scale factor was specifically correlated to the PHQ-9, the GAD-7, and the SSQ. This research adds the evidence to support the JBFS-SF as a clinically useful measure for assessing personality characteristics.